Sodium Naphthalene‐2, 6‐dicarboxylate: An Anode for Sodium Batteries. Issue 19 (12th September 2019) - Cabañero, Joel M.; Pimenta, Vanessa; Cannon, Kieran C.; Morris, Russell E.; Armstrong, A. Robert
Abstract: The conjugated dicarboxylate sodium naphthalene‐2, 6‐dicarboxylate (Na2 NDC) was prepared by a low‐energy‐consumption reflux method, and its performance as a negative electrode for sodium‐ion batteries was evaluated in electrochemical cells. The structure of Na2 NDC was solved for the first time (monoclinic P 21 / c ) from powder XRD data and consists of π‐stacked naphthalene units separated by sodium–oxygen layers. Through an appropriate choice of binder and conducting carbon additive, Na2 NDC exhibited a reversible two electron sodium insertion at approximately 0.4 V (vs. Na + /Na) with remarkably stable capacities of approximately 200 mAh g −1 at a rate of C/2 and good rate capability (≈133 mAh g −1 at 5 C). In parallel, the high thermal stability of the material was demonstrated by high‐temperature XRD: the framework remained intact to above 500 °C. Abstract : Sodium battery anodes : The conjugated dicarboxylate sodium naphthalene‐2, 6‐dicarboxylate (Na2 NDC) is prepared by a low‐energy‐consumption reflux method, and its performance as a negative electrode for sodium‐ion batteries is evaluated in electrochemical cells.